Determination of the isotonicity 1 % solution of sodium 2-((4-amino-5-thiophen-2-ylmethyl)-4H-1,2,4-triazole-3-yl)thio)acetate - D. L. Usenko; A. H. Kaplaushenko; B. O. Varynskyi (Zaporozhye State Medical University, 2024)
The aim of the work is to justify the composition of a 1 % aqueous solution of sodium 2-((4-amino-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazole-3-yl)thio)acetate for parenteral use. Materials and methods. The osmolality study of a 1 % solution of sodium 2-((4-amino-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazole-3-yl)thio)acetate was conducted using the cryoscopic method according to the State Pharmacopoeia of Ukraine (2.2.35). The calculations were based on measuring the depression of the crystallization temperature of the 1 % solution of sodium 2-((4-amino-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazole-3-yl)thio)acetate, 0.9 % NaCl solution, and high-purity water (Q3). The measurements of crystallization temperature were performed using a Beckman TL-1 thermometer, which allows for research with high precision up to ± 0.005 °C, making it valuable and most effective for studying isotonic concentration. Results. Temperature measurements of the crystallization of a 1 % solution under investigation, a 0.9 % NaCl solution, and high-quality purified water were conducted. Calculations of isotonic concentration were performed based on the measurement results. Conclusions. Based on the obtained experimental data on the depression of the crystallization temperature and the calculations, the amount of sodium chloride necessary for the preparation of an isotonic 1 % aqueous solution of AFI sodium 2-((4-amino-5-thiophen-2-ylmethyl)-4H-1,2,4-triazole-3-yl)thio)acetate for parenteral use was established.